An Update Review to Cast Light on the Possible Role of Altered Oropharyngeal Microbiota in Differentiating True Psychosis from Malingered Psychosis in a Forensic Psychiatric Setting - Mohsen Khosravi; Domenico De Berardis; Sahel Sarabandi; Sakineh Mazloom; Amir Adibi; Negin Javan; Zahra Ghiasi; Mohammad Nafeli; Negar Rahmanian (Mental Illness)
Over the past few years, malingered psychosis has had a progressive occurrence since a great deal of attention has been directed to the closures of long-stay psychiatric institutions and care in the community. Therefore, malingered psychosis needs to be identified to conduct precise forensic assessments and prevent miscarriages of justice and misuse of restricted healthcare resources. Although, over the past decades, researchers have introduced a number of workable psychometric strategies and tools for diagnosing true psychosis, it is still sometimes challenging to differentiate between true and malingered psychosis. Hence, identifying reliable and innovative diagnostic alternatives seems crucial. Accordingly, a summary of gathered evidence is provided by the present review for enhancing future evaluation of oropharyngeal microbiome composition as a practical indicator for diagnosing true psychosis in a forensic psychiatric setting. As per the systematic search terms (namely, “diagnostic marker,” “oropharyngeal microbiome,” “forensic psychiatric setting,” “psychosis,” and “oropharyngeal microbiota”), relevant English publications were searched from January 1, 1980, to September 15, 2023, in Scopus, the Web of Science, Embase, Cochrane Library, PubMed, and Google Scholar databases. Finally, eight articles were included in the present review. Also, we adopted the narrative technique so that the material synthesis leads to a cohesive and compelling story. The results revealed that the periodontal disease and saliva microbiome were possibly associated with true psychosis. Thus, since oropharyngeal microbial compositions are highly different among healthy controls and patients with true psychosis, future research can take advantage of saliva to differentiate between fake and true fake psychosis throughout the initial stages of forensic psychiatric assessment. As a substrate of interest, saliva could also be used for characterizing the various stages of psychosis under a forensic psychiatric setting.